REKONSTRUKSI TARI BARIS MAGPAG YEH DI SUBAK TEGAN DESA ADAT KAPAL KECAMATAN MENGWI KABUPATEN BADUNG - Ni Luh Putu Wiwin Astari; I Ketut Gede Rudita; Ni Dewi Septiandriani (UNHI PRESS, 2022)
ABSTRACT Reconstruction is the return of something to its original place, the compilation or redrawing of existing materials and rearranged as it was or the original incident. Various arts are deliberately preserved for ceremonial purposes. Dance in Bali is closely related to religious processions. It is even worth believing that the age of dance standards is as old as the establishment of Hinduism. Sacred dances that are preserved for ceremonial purposes in religious processes cause Balinese arts to be preserved, such as: the Magpag Yeh Baris Dance in Kapal Village, Mengwi District, Badung Regency. Sensitivity to external influences needs attention so that the development and survival of the Baris Magpag Yeh Dance in modern times does not deviate from its parent which has a clear identity, namely Hinduism. A.A Bagus Sudarma Magpag Yeh's line dance in Kapal Village is now the result of reconstruction. The Baris Magpag Yeh dance is a sacred dance performed on sasih kapitu in Subak Tegan, Kapal Adat Village, which has existed since the 16th century AD. This is evidenced by the history of the origin of this dance based on the Sri Aji Kresna Kepakisan inscription dated 1667 AD. The Baris Magpag Yeh dance is a dance that is staged as an expression of gratitude for the community for the blessing of water. After every performance of the Baris Magpag Yeh dance, rain or big water from the upstream of Lake Beratan appears in torrents. In general, the Baris Magpag Yeh Dance is usually accompanied by gamelan gong gede, while the Baris Magpag Yeh Dance in Kapal village is accompanied by gamelan gong kebyar or accompanied by gamelan baleganjur. This dance has a symbolic function to illustrate God's activities such as images or illustrated in paintings or statues of Shiva Nataraja. ABSTRAK Rekonstruksi adalah pengembalian sesuatu ketempatnya yang semula, penyusunan atau penggambaran kembali dari bahan-bahan yang ada dan disusun kembali sebagaimana adanya atau kejadian semula. Beraneka ragam kesenian secara sengaja dipelihara untuk kepentingan upacara. Seni Tari di Bali sangat erat kaitannya dengan prosesi keagamaan. Bahkan layak dipercaya bahwa usia pakem tari sama tuanya dengan penetapan Agama Hindu. Tari-tarian sakral yang dipelihara untuk kepentingan upacara dalam psoses keagamaan menyebabkan kesenian Bali tetap dijaga pelestariannya seperti halnya: Tari Baris Magpag Yeh yang ada di Desa Kapal, Kecamatan Mengwi, Kabupaten Badung. Kepekaan terhadap pengaruh-pengaruh luar perlu mendapatkan perhatian agar perkembangan dan kelangsungan hidup Tari Baris Magpag Yeh tersebut dalam jaman modern ini tidak menyimpang dari induknya yang mempunyai identitas yang jelas yaitu Agama Hindu. A.A Bagus Sudarma tari baris Magpag Yeh yang ada di Desa Kapal sekarang merupakan hasil rekonstruksi. Tari Baris Magpag Yeh merupakan tari sakral yang dipetaskan pada sasih kapitu di Subak Tegan Desa Adat Kapal yang sudah ada dari abad ke-16 Masehi. Hal tersebut dibuktikan dengan sejarah asal mula tarian ini berdasarkan prasasti Sri Aji Kresna Kepakisan berangka tahun 1667 Masehi. Tari baris magpag yeh ini merupakan tarian yang dipentaskan sebagai ucapan rasa syukur masyarakat terhadap berkah berupa air.Setiap usai digelar pementasan tari Baris Magpag Yeh, hujan atau air besar dari hulu Danau Beratan muncul dengan deras. Pada umumnya Tari Baris Magpag Yeh biasanya diiringi oleh gamelan gong gede, sementara Tari Baris Magpag Yeh di desa Kapal diiringi oleh gamelan gong kebyar atau diiringi oleh gamelan baleganjur. Tari ini memiliki fungsi simbolik untuk mengilustrasikan aktivitas Tuhan seperti gambaran atau diilustrasikan dalam lukisan atau patung Siwa Nataraja.